Use of historical data to assess the occurrence of floods in small watersheds in the French Mediterranean area - Payrastre, O.; Gaume, E.; Andrieu, H. (Advances in Geosciences, 2005)
The results of an investigation on historical floods in four watersheds of the Aude region in France are presented herein. Using both, archive documents and field investigations, the discharges of the main historical floods could be estimated for a period ranging from one to two centuries. The use of this data, in addition to systematic discharge measurements (continuous series of about 30 years in each case) shows that the calibration of Gumbel and EVII distributions is highly modified by using historical data, despite of the poor accuracy of discharge estimations for historical floods. In some cases, it is also possible, with a simple test using historical data, to exclude a statistical distribution (Gumbel in the presented case) which is not adapted to represent both historical and systematic data samples. Lastly, the historical data gathered highlights important differences in flood intensities among the four studied watersheds, differences that have now to be explained.